Production method of composite body of naturally-derived minute material and synthetic resin, and composite body of naturally-derived minute material and synthetic resin

JP2025041076APending Publication Date: 2025-03-26TOTTORI INST OF IND TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023148145
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-13
Publication Date
2025-03-26

AI Technical Summary

Benefits of technology

【0025】 以上述べたように、本発明によれば、天然由来の微細材料を用い、有機溶媒を使用せず、従来法よりも簡単な方法で、天然由来の微細材料が合成樹脂中に均質に分散した天然由来の微細材料と合成樹脂との複合体の製造方法を提供することができ、さらに、天然由来の微細材料と合成樹脂との複合体を提供することができるようになる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025041076000001_ABST
    Figure 2025041076000001_ABST
Patent Text Reader

Abstract

To provide a production method of a composite body of a naturally-derived minute material such as a chitin nanofiber, a chitosan nanofiber, a cellulose nanofiber or the like and a synthetic resin, and a composite body of a naturally-derived minute material and a synthetic resin produced by the production method.SOLUTION: A production method of a composite body of a naturally-derived minute material and a synthetic resin of the present invention includes: a step 10 of mixing a dispersion aqueous solution 11 of the naturally-derived minute material and a surfactant 12, and preparing a mixed solution 13 of the naturally-derived minute material and a surfactant; a step of forming a composite fiber body 17 which is composed of the naturally-derived minute material attached to a fiber body of the synthetic resin by making the fiber body 15 made of the synthetic resin impregnated in, or coated with, the mixed solution 13 of the naturally-derived minute material and the surfactant and succeedingly drying; and a step 22 of pulverizing the composite fiber body 17 and succeedingly injection molding and forming the composite body of the naturally-derived minute material and the synthetic resin.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a composite of a synthetic resin and a naturally occurring fine material, such as chitin nanofiber, chitosan nanofiber, or cellulose nanofiber, and to a composite of a synthetic resin and the naturally occurring fine material produced by this method, which is contained in the form of a flat fibrous body. [Background technology]

[0002] In recent years, various technologies have been developed to achieve carbon neutrality, and the reduction of petroleum-derived plastics through the use of renewable biomass plastics and natural resources is also being promoted. As one of the efforts, natural fine materials such as chitin nanofibers (hereinafter referred to as "chitin NF") derived from crustaceans and cellulose nanofibers (hereinafter referred to as "CNF") derived from plants are added to resins to reduce petroleum-derived materials, suppress dimensional changes of resins due to heat, and improve their strength. In addition, chitosan nanofibers (hereinafter referred to as "chitosan NF") obtained by deacetylating chitin NF are also known as natural fine materials, and chitin NF and chitosan NF have high biocompatibility, so there are high expectations in the medical and pharmaceutical industries.

[0003] Generally, melt-kneading is performed when compounding resins and additives, and this melt-kneading has the advantage that the number of steps is small and continuous processing is possible. However, if natural fine materials containing water are used as is, agglomerates are generated during kneading, which creates a problem in dispersibility. Since various natural fine materials are sold in a state dispersed in water, they need to be dried before melt-kneading, but the fine materials also aggregate during this drying process.

[0004] In order to improve the dispersibility of such various naturally derived fine materials in resin components, various technologies have been developed. For example, since CNF is a highly water-absorbent material with many hydroxyl groups on the surface, the Kyoto Process disclosed in Non-Patent Document 1 discloses a method in which CNF is hydrophobically modified by acetylation, and the hydrophobically modified CNF is kneaded in a resin that has been thermally melted by a twin-screw extruder. According to this Kyoto Process, the hydrophobically modified CNF is defibrated during melt kneading with the resin, so that a composite material that is uniformly dispersed in the resin can be obtained. In addition, Non-Patent Document 2 discloses a method in which, in order to prevent aggregation during drying of the fine material containing moisture, t-butanol is added to an aqueous solution in which the fine material is dispersed, mixed, centrifuged, and the precipitate is collected, and the process is repeated about 10 times, and further freeze-dried to obtain a dry powder of the fine material. In this method, it is said that a reduced pressure of more than one week is preferable for sufficient drying, and there is a problem that one treatment takes a long time.

[0005] In addition, Non-Patent Document 3 shows an example of producing a chitosan NF-epoxy resin composite material by utilizing the amino group of chitosan NF, adding ethylene glycol diglycidyl ether (EGDG) to an aqueous solution of chitosan NF, processing it with a rotary disk mill to defibrate it, freeze-drying it, adding a curing agent triethylenetetramine, and heating it. Furthermore, Non-Patent Document 4 shows an example of producing a test piece made of a PP / CNF composite resin by adding a polyglycerol fatty acid ester as a surfactant to an aqueous dispersion of CNF to partially hydrophobize the surface of the CNF, melt-kneading it with polypropylene (hereinafter sometimes referred to as "PP"), and further injection molding it. In addition, Non-Patent Document 5 shows an example of producing a composite material in which CNF is dispersed in PLA by spray-drying an aqueous dispersion of CNF with a spray dryer and kneading it with polylactic acid (hereinafter sometimes referred to as "PLA") using a Labotrust mill and a twin-screw extrusion kneader.

[0006] Furthermore, Patent Document 1 discloses a method in which an aqueous dispersion of fine cellulose (CNF) is defibrated in an organic solvent to obtain an organic solvent dispersion of CNF, the organic solvent in this CNF organic solvent dispersion is replaced with water to obtain an aqueous dispersion of CNF, and the aqueous dispersion of CNF is mixed with thermoplastic resin particles, which are then dried to recover finely powdered composite particles.

[0007] Patent Document 2 discloses an invention of a resin composition having (A) a dried cellulose nanofiber (CNF) prepared from CNF, (B) an acid-modified polypropylene, and (C) a polyolefin resin, in which the dried CNF is cellulose having a crystalline form of type I, made from any one of wood pulp, cotton, linters, hemp, bacterial cellulose, and parenchyma cell fibers, contains, as an organic component, an anionic or nonionic surfactant, or a mixture thereof, which is soluble and dispersible in water, ethanol, or a water-soluble alcohol such as methanol, in an amount of 0.05 to 30 mass% of the dry weight of the dried CNF, and has a degree of polymerization (measured by a viscosity method using a copper ethylenediamine solution) of 100 or more and 1,500 or less, and is characterized in that the loading amount of the dried CNF is 5 mass% or less of the entire resin composition, the tensile elongation at break is 600% or more, and the tensile strength at break is 30 MPa or more. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Patent Publication No. 2021-155750 [Patent Document 2] Patent No. 6889358 [Patent Document 3] Patent No. 4370416 [Non-patent literature]

[0009] [Non-Patent Document 1] Introduction to the Kyoto Process [Retrieved August 12, 2023], <http: / / www.rish.kyoto-u.ac.jp / labm / wp-content / uploads / 2012 / 07 / cf1b30a5725ce3fd0d110d3376a0d314.pdf> [Non-Patent Document 2] Cellulose Materials Group Freeze-drying method for nanocellulose slurry by alcohol replacement [Retrieved August 12, 2023], <https: / / unit.aist.go.jp / ischem / ischem-clm / technical_point / technical_point3.html> [Non-Patent Document 3] "The 32nd Annual Conference of the Society of Plastics Processing" Abstracts C-212 [Non-Patent Document 4] "The 32nd Annual Meeting of the Society of Plastics Molding Engineering" Abstracts F-205 [Non-Patent Document 5] "Material Life Society Journal" Vol.28, No.1, p.12-21 Summary of the Invention [Problem to be solved by the invention]

[0010] According to the composite methods of various fine materials and resins disclosed in Non-Patent Documents 1 to 5 and Patent Documents 1 and 2, fine material composite resins in which various fine materials are well dispersed in resin can be obtained, but each requires chemical modification or separation and drying of various fine materials, making the manufacturing process complicated. Non-Patent Document 1 also discloses a method of producing a CNF sheet directly from an aqueous suspension of CNF, impregnating this CNF sheet with resin and compression molding it to produce a CNF-resin composite material, which has the advantages of being able to use thermosetting resins and being able to produce transparent films, but has the problems of being limited to liquid resins and being difficult to mold continuously.

[0011] Patent Document 3 discloses an invention for a bagasse fiber-reinforced resin material that can be injection molded using bagasse fiber, which is the residue remaining after squeezing all the cane juice out of sugarcane, and polypropylene (PP). However, the bagasse fiber used here has a fiber length in the range of 0.5 mm to 50 mm and does not fall into the category of fine materials, so there is no problem with condensation during drying of naturally derived fine materials as described above.

[0012] The inventors have conducted extensive research to solve the problems related to naturally occurring fine materials as described above, and as a result, have discovered that a composite material in which naturally occurring fine materials are uniformly dispersed can be produced by using an aqueous solution of the naturally occurring fine materials as is, without separating and drying the fine materials from the aqueous solution of the naturally occurring fine materials, and have thus completed the present invention.

[0013] In other words, the present invention aims to provide a method for producing a composite of naturally occurring fine material and synthetic resin, in which the naturally occurring fine material is homogeneously dispersed in the synthetic resin, by using naturally occurring fine material in a manner simpler than conventional methods, and to provide a composite of naturally occurring fine material and synthetic resin produced by this production method. [Means for solving the problem]

[0014] The method for producing a composite of naturally occurring fine material and synthetic resin of the present invention is characterized by comprising the steps of: mixing an aqueous dispersion of the naturally occurring fine material with a surfactant to prepare a mixed solution of the naturally occurring fine material and surfactant; impregnating or coating a synthetic resin fibrous body with the mixed solution of the naturally occurring fine material and surfactant, and then drying the same to form a composite fibrous body in which the naturally occurring fine material is attached to the synthetic resin fibrous body; and pulverizing the composite fibrous body and then extruding it to form a composite of the naturally occurring fine material and synthetic resin.

[0015] In the method for producing a composite of a naturally derived fine material and a synthetic resin according to the present invention, not only nanometer-sized natural fine materials such as cellulose nanofibers, chitin nanofibers, and chitosan nanofibers can be used as natural fine materials, but also micrometer-sized natural fine materials. All of these naturally derived fine materials are commercially available in a state dispersed in water, and commercially available materials can be used as they are. These naturally derived fine materials are highly hydrophilic due to the presence of many hydroxyl groups on the surface, so they disperse well in water, but they tend to aggregate when dried due to the influence of the hydroxyl groups. In addition, even if a synthetic resin fiber body is immersed in a dispersion solution of the naturally derived fine material, the wettability is poor, and the fiber body repels the aqueous solution. On the other hand, if an organic solvent such as alcohol is mixed into a dispersion solution of the naturally derived fine material, the wettability with the fiber body is improved while maintaining the dispersibility of the naturally derived fine material, but it is highly volatile and very difficult to handle, such as in terms of measures using local ventilation devices, so it is desirable to avoid using an organic solvent as much as possible.

[0016] Therefore, the method for producing a composite of a natural fine material and a synthetic resin of the present invention includes the steps of first mixing a dispersion solution of the natural fine material with a surfactant to prepare a mixed solution of the natural fine material and the surfactant, and then impregnating or coating a synthetic resin fiber body with the mixed solution of the natural fine material and the surfactant, followed by drying to form a composite fiber body in which the natural fine material is attached to the synthetic resin fiber body. In this first step, a surfactant is added to the aqueous solution of the natural fine material. This surfactant serves to make the natural fine material and the synthetic resin fiber body compatible, so that the natural fine material is stably dispersed in the aqueous solution and the wettability of the synthetic resin fiber body is improved.

[0017] Therefore, when a synthetic resin fiber body is immersed in an aqueous solution of a natural fine material, or when an aqueous solution of a natural fine material is applied to a synthetic resin fiber body, the natural fine material adheres to the synthetic resin fiber body in a large amount and in a well-dispersed state without hydrophobizing the natural fine material, and when this is dried, a composite fiber body can be obtained in which the natural fine material is uniformly dispersed and adhered to the synthetic resin fiber body in a large amount. The composite fiber body thus obtained is then crushed and extruded to form a composite of the natural fine material and synthetic resin of the present invention. The composite fiber body in which the natural fine material adheres to the synthetic resin fiber body can also be used for various purposes as necessary.

[0018] In addition, as an extrusion molding machine for extrusion molding, both single-screw extruders and twin-screw extruders can be used, but the composite fiber body obtained as an intermediate product in the present invention is a homogeneously dispersed and attached natural fine material and synthetic resin fiber body, so there is no need for melt kneading, and it is possible to produce a molded product of a composite of natural fine material and synthetic resin with sufficiently uniform characteristics by drying, pulverizing, and directly using a single-screw extruder. In addition, when a twin-screw extruder is used, the plasticization mechanism is complicated, such as heat generation due to friction and shear stress caused by the rotation of the screw, and there is also the problem that temperature control is more complicated than with a single-screw extruder.

[0019] In the method for producing a composite of a naturally occurring fine material and a synthetic resin according to the present invention, cellulose nanofibers, chitin nanofibers, or chitosan nanofibers can be used as the naturally occurring fine material. These naturally occurring fine materials are commercially available in the form of an aqueous solution in which they are already dispersed in water, and these aqueous solutions can be appropriately selected and used depending on the purpose.

[0020] In addition, in the method for producing a composite of a naturally derived fine material and a synthetic resin of the present invention, both ionic surfactants (cationic surfactants, anionic surfactants, amphoteric surfactants) and nonionic surfactants (nonionic surfactants) can be used as surfactants. However, foaming occurs during stirring, and the naturally derived fine material may overflow from the stirring vessel due to the foaming and be wasted. Therefore, it is preferable to use a nonionic surfactant, especially from the viewpoint of less foaming. In addition, since nonionic and anionic surfactants have the advantage of less aggregation, it is preferable to select an appropriate surfactant according to the type and concentration of the naturally derived fine material. In addition, since the use of cationic surfactants makes CNF more likely to aggregate, it is preferable to use other surfactants. Furthermore, in the method for producing a composite of a naturally derived fine material and a synthetic resin of the present invention, a mixture of multiple surfactants can also be used as appropriate.

[0021] The concentration of the surfactant varies depending on the type of surfactant, so the critical limit is not necessarily clear. However, if the concentration is too low, the effect of adding the surfactant will not be apparent, and if the concentration is too high, aggregation of the naturally occurring fine materials will occur more easily and there will be more foaming, so it is preferable to use a concentration of about 0.01 to 3.0 wt % of the total mixed solution of the aqueous solution of the naturally occurring fine materials and the surfactant.

[0022] In addition, in the manufacturing method of the composite of the naturally derived fine material and the synthetic resin of the present invention, it is preferable to use a thermoplastic resin as the synthetic resin fiber body. Thermoplastic resin is a plastic material that becomes plastic and moldable at a specific high temperature and solidifies when cooled, and is a widely used plastic material. As thermoplastic resins, various types such as polyethylene, acrylic resin, polyamide (nylon), polycarbonate, polylactic acid, polypropylene (PP), polystyrene, polyvinyl chloride, etc. are known. In the manufacturing method of the composite of the naturally derived fine material and the synthetic resin of the present invention, all of these well-known thermoplastic resins can be used, but PP in particular is the most preferable because it has good heat resistance, a small specific gravity and is light, high strength, excellent chemical resistance, and other properties among general-purpose resins, and is also manufactured in the form of a fiber body. When a thermoplastic resin is used as the synthetic resin fiber body, it becomes possible to obtain a homogeneous composite in which the naturally derived fine material and the synthetic resin are sufficiently dispersed and mixed even when a uniaxial molding machine is used. As the synthetic resin fibrous body, a synthetic resin nonwoven fabric, woven fabric, or knitted fabric can be used, but the nonwoven fabric is preferable as it is optimal for uniformly dispersing and attaching fine materials of natural origin.

[0023] The process of impregnating or coating the synthetic resin fibrous body with the mixed solution of the natural fine material and the surfactant and then drying may be performed once or multiple times. By repeating these processes multiple times, the amount of the synthetic resin natural fine material attached can be increased and the area where the natural fine material is not attached can be reduced, resulting in a composite body impregnated or attached with the natural fine material more uniformly.

[0024] In addition, the manufacturing method of the composite of the natural fine material and the synthetic resin of the present invention may include a step of crushing the composite fiber body with the natural fine material attached to the synthetic resin fiber body, pelletizing it, and then injection molding it to form a composite of the natural fine material and the synthetic resin. If such a method of forming pellets before injection molding is adopted, the composite fiber body with the natural fine material attached is crushed even at the pelletizing stage, so that an injection molded product is obtained in a state in which the natural fine material is dispersed in the synthetic resin in the form of flattened fiber bodies. Therefore, when the pellets formed in this way are injection molded, a composite of the natural fine material and the synthetic resin in which the natural fine material in the form of flattened fiber bodies is dispersed in the synthetic resin is obtained, so that the adhesion between the natural fine material and the synthetic resin is improved, and the tensile strength of the composite of the natural fine material and the synthetic resin obtained is increased. Effect of the Invention

[0025] As described above, according to the present invention, it is possible to provide a method for producing a composite of naturally occurring fine material and synthetic resin, in which the naturally occurring fine material is homogeneously dispersed in the synthetic resin, by using naturally occurring fine material without using organic solvents and in a manner simpler than conventional methods, and it is also possible to provide a composite of naturally occurring fine material and synthetic resin. [Brief description of the drawings]

[0026] [Figure 1] 1 is a diagram showing a method for producing a composite of naturally occurring fine material and synthetic resin according to the present invention. FIG. [Diagram 2] 1 is a photograph of a pulverized composite fiber body. [Diagram 3] 1 is a photograph of a composite fiber body that has been pelletized after pulverization. [Figure 4] 1 is a photograph showing the shape of a dumbbell-shaped test piece for a tensile test. [Diagram 5] FIG. 5(a) is an electron microscope photograph of sample D, and FIG. 5(b) is an electron microscope photograph of sample G. [Figure 6]1 is a graph showing the results of tensile tests on dumbbell-shaped test pieces of samples A to G and L. [Figure 7] FIG. 7(a) is an electron microscope photograph of sample J, and FIG. 7(b) is an electron microscope photograph of sample K. [Figure 8] 1 is a graph showing the results of tensile tests on dumbbell-shaped test pieces of samples A, H to K, and M. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0027] The method for producing a composite of naturally occurring fine material and synthetic resin according to the present invention will be described in detail below using various experimental examples. However, the various experimental examples shown below are examples for embodying the technical idea of ​​the present invention, and are not intended to limit the present invention to those shown in these experimental examples. The present invention can be equally applied to other embodiments included in the scope of the claims.

[0028] The outline of the method for producing a composite of naturally derived fine materials and synthetic resins according to the present invention will be described with reference to FIG. 1. The naturally derived fine materials used in the present invention, such as cellulose nanofibers, chitin nanofibers, and chitosan nanofibers, are all commercially available in a state dispersed in water, and the commercially available materials are used as they are. These naturally derived fine materials can be used not only in nanometer size but also in micrometer size. First, in the first step 10 of preparing a mixed solution of naturally derived fine materials and surfactants, a predetermined amount of an aqueous solution 12 of a surfactant prepared to an appropriate concentration is added to an aqueous dispersion 11 of naturally derived fine materials diluted with water as necessary, to prepare a mixed solution 13 of naturally derived fine materials and surfactants at a predetermined concentration. At this time, the mixed solution 13 is thoroughly stirred, but it is desirable to suppress foaming. As a result, a mixed solution 13 in which the naturally derived fine materials and surfactants are dispersed is obtained.

[0029] Next, in the immersion step 14, a synthetic resin fiber body 15 of a predetermined size, preferably a nonwoven fabric made of PP, is immersed in the mixed solution 13 of the naturally derived fine material and the surfactant for a predetermined time, and the synthetic resin fiber body 15 is sufficiently impregnated with the mixed solution 13. Next, in the drying step 16, the synthetic resin fiber body 15 impregnated with the mixed solution 13 is taken out and dried at room temperature for 24 hours or more to obtain a synthetic resin composite fiber body 17 having the components of the mixed solution 13 attached to its surface. At this time, the naturally derived fine material is attached in a flat shape, so that the physical strength, for example, tensile strength, of the obtained synthetic resin molded product 23 is improved. In addition, in this specification, "room temperature" means a room temperature (5°C to 35°C) in a natural state without cooling or heating.

[0030] Next, a pelletizing process 20 is carried out by extrusion to produce synthetic resin pellets 21 containing the components of the mixed solution. Thereafter, the synthetic resin pellets 21 containing the components of the mixed solution are molded into a predetermined shape through an injection molding process 22 using, for example, an injection molding machine to obtain a synthetic resin molded product 23 to which the components of the mixed solution are attached. It is possible to omit the pelletizing process 20, but it is preferable to employ the pelletizing process 20 because the pelletizing process 20 allows the material to be smoothly supplied to the molding machine.

[0031] [CNF composite] First, we investigated the adhesion state of CNF when a PP nonwoven fabric was immersed in a commercially available aqueous solution of CNF. The PP nonwoven fabric (hereinafter referred to as "PP nonwoven fabric") was a nonwoven fabric roll (product name, purchased from Trusco Nakayama Co., Ltd.) with a basis weight of 30 g / cm. 2The nonwoven fabric roll was cut to 150 mm x 150 mm and used. As the CNF raw material, a 2 wt% aqueous solution of Binfis FMa-10002 (trade name, manufactured by Sugino Machine Co., Ltd.) was used as the stock solution, which was diluted with ion-exchanged water and used in various experiments. As the surfactant, a fluorine-based surfactant, Surflon S-243 (trade name, manufactured by AGC Sei Chemical Co., Ltd.), and a polyoxyethylene alkyl ether surfactant, Newcol (registered trademark) 2303 (trade name, manufactured by Nippon Nyukazai Co., Ltd.), were used in appropriate combination. Note that all of these surfactants are nonionic surfactants.

[0032] In experiments 1 to 6, a mixed solution of CNF and surfactant was used, with a CNF concentration of 0.5 to 1.0 wt% and 0.01 wt% S-243 added as a surfactant. The immersion time was 10 seconds, and the immersion was performed once. After immersion, the sample was dried at room temperature for a day and night, the weight increase was measured, and the CNF content after composite was measured using the following formula (I). TIFF2025041076000002.tif17136

[0033] Similarly, in Experiments 7 to 12, the CNF content after compounding was measured in the same manner as in Experiments 1 to 6, except that the surfactant S-243 was 0.02 wt%. Furthermore, in Experiments 13 and 14, the CNF concentration was 0.8 wt% (Experiment 13) to 1.0 wt% (Experiment 14), and the weight increase was measured in the same manner as in Experiments 1 to 6, except that two types of surfactants, S-243 and 2303, were used simultaneously at 0.03 wt% and 0.02 wt%, respectively, and the weight increase was measured according to the above formula (I). The results of Experiments 1 to 14 are summarized in Table 1.

[0034] [Table 1]

[0035] From the results shown in Table 1, the following can be seen. In each of the cases of Experiments Nos. 1 to 6 and 7 to 12, when the concentration of the surfactant is constant, the CNF content in the composite fiber after compounding increases with an increase in the CNF concentration in the mixed solution of CNF and surfactant. Also, when the CNF content is constant, the CNF content in the composite fiber after compounding increases with a higher surfactant concentration in the mixed solution of CNF and surfactant. Furthermore, from the results of Experiments Nos. 13 and 14, even when multiple types of surfactants are used in combination, the CNF content in the composite fiber after compounding increases with an increase in the CNF concentration in the mixed solution of CNF and surfactant, and also, the CNF content in the composite fiber after compounding increases with a higher surfactant concentration in the mixed solution of CNF and surfactant.

[0036] Therefore, from the results of another preliminary experiment omitted from Table 1, if the surfactant concentration in the mixed solution of CNF and surfactant is 0.001wt% or more, the effect of increasing the CNF content in the composite fiber after composite is achieved, and since a higher surfactant concentration leads to higher costs and the CNF is more likely to aggregate, it is preferable to set the surfactant concentration at 0.01 to 3.0wt%. A more preferable surfactant concentration is thought to be 0.05 to 1.0wt%.

[0037] In addition, in the above experiments 1 to 12, the immersion time in the mixed solution of CNF and surfactant was 10 seconds and the immersion was once, while in the above experiments 13 and 14, the immersion time was 60 seconds and the immersion was once. However, regardless of the immersion time, even if the immersion was multiple times (immersing once for a specified time, drying overnight at room temperature, and then immersing again for a specified time and drying, this cycle is repeated a specified number of times), it was confirmed that the CNF content in the composite fiber body after composite formation increased with the number of immersions.

[0038] [Combination of chitosan NF] Next, the adhesion state of chitosan NF when PP nonwoven fabric was immersed in an aqueous solution of chitosan nanofiber (chitosan NF) was investigated. First, the same PP nonwoven fabric and surfactant as those in Experiments 1 to 14 were used, and a 10 wt% aqueous solution of Binfis-08010 (trade name, manufactured by Sugino Machine Co., Ltd.) was used as the raw chitosan NF solution, which was diluted with ion-exchanged water and used for various experiments. In Experiments 15 to 20, a mixed solution of chitosan NF and surfactant was used, in which the chitosan NF concentration was 0.5 to 1.0 wt% and S-243 was added as the surfactant to be 0.01 wt%, and the immersion time was 10 seconds and the number of immersions was 1 time. After immersion, the fabric was dried at room temperature for a day and night, the weight increase was measured, and the chitosan NF content after the composite was measured using the same formula as the above formula (I).

[0039] Furthermore, in Experiments 27 and 28, the chitosan NF concentration was 1.0 wt%, and two types of surfactants were used simultaneously, S-243 at 0.02 wt% and 2303 at 0.01 wt% (Experiment 27) or S-243 at 0.03 wt% and 2303 at 0.02 wt% (Experiment 28). The weight gain was measured in the same manner as in Experiments 15 to 20, and the weight gain was measured using the same formula as the above formula (I). The results of Experiments 15 to 28 are summarized in Table 1.

[0040] [Table 2]

[0041] The results shown in Table 2 reveal the following. The results shown in Experiments 15 to 28 using chitosan NF showed the same tendency as Experiments 1 to 14 using CNF shown in Table 1. That is, when the surfactant concentration was constant, the chitosan NF content in the composite fiber after composite increased with an increase in the chitosan NF concentration in the mixed solution of chitosan NF and surfactant, and when the chitosan NF content was constant, the chitosan content in the composite fiber after composite increased with a higher surfactant concentration in the mixed solution of chitosan NF and surfactant, and further, even when a mixture of multiple types of surfactants was used, the chitosan NF content in the composite fiber after composite increased with an increase in the chitosan NF concentration in the mixed solution of chitosan NF and surfactant.

[0042] Therefore, based on the results of another preliminary experiment omitted from Table 2, if the surfactant concentration in the mixed solution of chitosan NF and surfactant is 0.001 wt% or more, the effect of increasing the chitosan NF content in the composite fiber after composite is achieved, and further, since a higher surfactant concentration increases the cost and makes the chitosan NF more likely to aggregate, it is preferable to set the surfactant concentration at 0.01 to 3.0 wt%. A more preferable surfactant concentration is thought to be 0.05 to 1.0 wt%.

[0043] [Combination of chitin NF] Next, we investigated the adhesion state of chitin nanofiber (chitin NF) when PP nonwoven fabric was immersed in an aqueous solution of chitin NF. As the PP nonwoven fabric, a nonwoven fabric roll (product name, purchased from Trusco Nakayama Co., Ltd.) with a basis weight of 30 g / cm was used. 2 50g / cm 2 and Pipyrol (product name, purchased from Sankei Co., Ltd.) 70 g / cm 2The three types of nonwoven fabric rolls were cut into 150 mm x 150 mm pieces and used. As the chitin NF raw material, a 10 wt% aqueous solution of Binfis SFo-20010 (trade name, manufactured by Sugino Machine Co., Ltd.) was used as the stock solution, which was diluted with water and used in various experiments. In experiments 29 to 33, the surfactants were the same as those in experiments 1 to 14, and the S-243 concentration and 2303 concentration in the mixed solution of chitin NF and surfactant were constant at 0.03 wt% and 0.02 wt%, respectively, and the chitin NF concentration in this mixed solution was constant at 1.0 wt%.

[0044] In experiments 29 and 30, the nonwoven fabric weight was 30 g / cm 2 In experiment number 29, the nonwoven fabric was immersed in the mixed solution of chitin NF and surfactant for 60 seconds, and in experiment number 30, the nonwoven fabric was immersed for 10 seconds. The chitin CNF content after the composite was measured. In experiments 31 and 32, the nonwoven fabric was 50 g / cm 2 In experiment number 31, the immersion time in the mixed solution of chitin NF and surfactant was 60 seconds, and in experiment number 32, the immersion time was 10 seconds, and the chitin CNF content after the composite was measured. In experiment number 33, the nonwoven fabric was 70g / cm 2 The chitin NF content after the composite was measured using the same formula as formula (I) above. The results are summarized in Table 3 below.

[0045] [Table 3]

[0046] The results shown in Table 3 reveal the following. That is, in both cases where the immersion time was 60 seconds (Experiment Nos. 29, 31, and 33) and where the immersion time was 10 seconds (Experiment Nos. 30 and 32), the chitin NF content after compounding decreased as the nonwoven fabric basis weight increased. This indicates that the nonwoven fabric basis weight is an indicator of the degree of overlap of the fibers in the nonwoven fabric, i.e., the density, and therefore it is believed that the greater the nonwoven fabric basis weight, the more difficult it becomes for the nonwoven fabric to be impregnated with the mixed solution of chitin NF and surfactant, resulting in a decrease in the chitin NF content after compounding.

[0047] It should be noted that, although the results of the experiment were conducted on chitin NF and PP nonwoven fabric, this tendency is believed to be a phenomenon that occurs in the same way whether the natural fine material is CNF or chitosan NF. Therefore, when manufacturing a composite of natural fine material and synthetic resin, in order to increase the content ratio of natural fine material, it is preferable that the weight of the nonwoven fabric is not too large. Therefore, it is recommended to use a woven fabric with a weight of 30 g / cm that is often available on the market. 2 In this experiment, the nonwoven fabric was immersed in the mixed solution, but the mixed solution may be applied to the nonwoven fabric.

[0048] [Crushing, pelletizing, and molding process] In order to use the nonwoven fabrics with various NFs attached thereto as products of various shapes, it is necessary that they can be molded by extrusion molding or injection molding. Therefore, the PP nonwoven fabric and the composite fiber body in which various natural fine materials are attached to the PP nonwoven fabric were crushed using a crusher (MGL2-100-J (trade name), manufactured by Matsui Seisakusho Co., Ltd.), and the crushed material was fed into a single-screw extruder (FRP-V32 (trade name), manufactured by Myojo Metal Industries Co., Ltd.) and pelletized by extrusion processing. Then, a dumbbell-shaped test piece for tensile testing was manufactured using an injection molding machine (NEX80-9E (trade name), manufactured by Nissei Plastics Co., Ltd.) to measure the tensile properties. The extrusion processing conditions were a processing temperature of 190°C and a screw rotation speed of 18.5 rpm. The injection molding conditions for the composite material with added maleic anhydride modified polypropylene (MAHPP) described below were: injection temperature 190°C, mold temperature 40°C, injection speed 60mm / s, injection pressure 80MPa, holding pressure 40MPa, injection time 30s, and cooling time 30s. The injection molding conditions were: injection temperature 190°C, mold temperature 40°C, injection speed 60mm / s, injection pressure 80MPa, holding pressure 40MPa, injection time 30s, and cooling time 30s. The state of the composite fiber after fine grinding is shown in Figure 2, the state of the pellets in Figure 3, and the shape of the dumbbell-shaped test piece for the tensile test in Figure 4.

[0049] [Various experimental examples using chitin NF] As examples of various experiments using chitin NF, the same aqueous solution of chitin NF used in experiments 29 to 33 was used as a naturally derived fine material, and a mixed solution of chitin NF and an aqueous solution of IPA was prepared using water-soluble isopropyl alcohol (IPA) as an organic solvent instead of a surfactant, and the same basis weight of 30 g / cm was applied to this mixed solution as used in experiments 29 and 30. 2 The PP nonwoven fabric was cut to 300 mm x 500 mm and soaked for a specified period of time to adjust the amount of chitin NF attached.

[0050] Sample A is a sample made by pulverizing PP nonwoven fabric alone and then injection molding it to produce a test piece for tensile testing, Sample B is a sample made by pulverizing chitin NF-attached PP nonwoven fabric produced using PP nonwoven fabric, an aqueous solution in which chitin NF is dispersed, and IPA, and then extruding and pelletizing it to produce a test piece for tensile testing, and Samples C to E are samples made by adding maleic anhydride-modified polypropylene (MAHPP) to enhance the compatibility of chitin NF and PP, and by changing the molding conditions in the same manner as in Test Examples A to D to produce a test piece for tensile testing. These Samples A to E are an example that does not contain chitin NF (Sample A) and an example that contains chitin NF but uses a solvent containing alcohol (Samples B to E), and all of them correspond to comparative examples.

[0051] Sample F, shown as another experimental example, is a sample produced by injection molding commercially available PP pellets (J-750HP (trade name), manufactured by Prime Polymer Co., Ltd.), and sample G is a sample produced by mixing PP pellets and chitin NF powder and injection molding the mixture. The chitin NF powder was obtained by replacing the solvent in a commercially available chitin NF dispersion (SFo-20002 (trade name), manufactured by Sugino Machine Co., Ltd.) with ethanol, removing the supernatant by centrifugation and vacuum drying, and then pulverizing the mixture, with the amount of ethanol added being 10 times the weight of the chitin NF dispersion. These samples F and G also correspond to comparative examples.

[0052] Furthermore, as sample L corresponding to the embodiment of the present invention, a test piece for a tensile test was manufactured using the same PP nonwoven fabric as used in samples A to F, MAHPP, and a mixed solution containing an aqueous solution of chitin NF as a natural fine material and surfactants (S-243 and 2303) as used in test numbers 29 to 33. The chitin NF content in the mixed solution was 2.0 wt%, the content of S-243 as a surfactant was 0.03 wt%, and the content of 2303 as a surfactant was 0.02 wt%. The compositions of samples A to G and L subjected to the above-mentioned respective injection moldings are summarized in Table 4.

[0053] [Table 4]

[0054] Furthermore, the results of observing the internal structure of injection-molded samples D and G using an electron microscope are shown in Figure 5. Figure 5(a) is an electron microscope photograph of sample D, and Figure 5(b) is an electron microscope photograph of sample G. The chitin NF in sample D shown in Figure 5(a) was seen to be dispersed throughout the cross section in the form of fibers of several tens of μm to 100 μm, unlike the particulate form seen in sample G to which powdered chitin NF was added shown in Figure 5(b). Therefore, it is considered that the sample using chitin NF-attached PP has better dispersibility.

[0055] Next, tensile tests were performed using dumbbell-shaped test pieces of the molded samples A to G and L, which had the shapes shown in Figure 4. Figure 6 shows the results of the tensile tests on the dumbbell-shaped test pieces of various samples. The results shown in Figure 6 reveal the following. In other words, in sample B, which contains 5 wt% chitin NF relative to the total weight, a decrease in tensile strength and tensile modulus was observed compared to the test piece of sample A, which uses PP nonwoven fabric itself. On the other hand, in samples C to E, in which MAHPP was added to increase the compatibility of chitin NF and PP and the molding conditions were further changed, as the chitin NF content increased to 7.2 wt% (sample C), 20.0 wt% (sample D), and 31 wt% (sample E), the tensile strength maintained about 95% of that of sample A, and no significant decrease was observed, but the tensile modulus increased with the increase in the chitin NF content. Test pieces F and G are examples in which commercially available PP pellets themselves were used (test piece F) and examples in which commercially available PP pellets and powdered chitin NF were used. However, the tensile strength and tensile modulus of elasticity of both were lower than those of test pieces A to E, and it was estimated that the addition of chitin NF had no substantial effect on the results of test pieces F and G.

[0056] On the other hand, in the case of sample L corresponding to the embodiment of the present invention, the tensile strength was slightly increased compared to the test piece of sample A using the PP nonwoven fabric itself, and the tensile modulus was significantly increased. Furthermore, compared to the cases of samples B to E using the mixed solution containing an organic solvent (IPA), both the tensile strength and the tensile modulus of elasticity of sample L were larger, and compared to the case of sample D, in which the content ratio of MAHPP and the content ratio of chitin NF in the test piece are almost the same, it was confirmed that both the tensile strength and the elongation tensile modulus of elasticity of sample L were larger. This tendency was also observed in the case of sample E, in which the content ratio of chitin NF was higher than that of sample L. From the above, it was confirmed that in the molded products (samples B to E and L) obtained by pelletizing the chitin NF-attached PP nonwoven fabric after fine grinding and extrusion molding, it was possible to prepare test pieces with better physical properties by using a surfactant rather than using the mixed solution containing an organic solvent (IPA).

[0057] In addition, from the results shown in Figure 6, it can be seen that the test pieces of samples B to E, which were made using a mixed solution containing an organic solvent (IPA), have superior physical properties compared to the test piece of sample G, which was simply mixed with powdered chitin NF. In particular, in comparison with the test piece of sample G, the electron microscope photograph of the test piece of sample G shown in Figure 5(b) shows large clumps of chitin NF, and it is thought that these clumps are the starting point for the breakage of test piece G, resulting in a significant decrease in tensile strength. On the other hand, in the electron microscope photograph of test piece D in Figure 5(a), no large clumps of chitin NF are seen, so it is thought that there is no decrease in tensile strength in test piece D.

[0058] [Experimental example using CNF] In the various experimental examples using chitin NF described above, a mixed solution of chitin NF and an IPA aqueous solution was prepared using water-soluble IPA, which is an organic solvent, and a PP nonwoven fabric was immersed in the mixed solution to prepare the product. From these various experimental examples, it was found that when a PP nonwoven fabric was immersed in a mixed solution of chitin NF and an IPA organic solvent for a predetermined time, the injection-molded molded products (samples B to E) had properties comparable to those of the molded product of sample A, which does not contain chitin NF. On the other hand, according to this method, the IPA concentration in the mixed solution is 25 to 90 wt%, which requires a large amount of organic solvent, so care must be taken in handling IPA, which is a hazardous material under the Fire Service Act, such as measures against volatility and flammability, and it is difficult to use it easily. Here, according to the present invention, a mixed solution of CNF (Binfis FMa-10010 (trade name, manufactured by Sugino Machine Co., Ltd.), CNF concentration in the raw material 10 wt%) and a surfactant was used, and dumbbell-shaped test pieces having the shape shown in FIG. 4 were manufactured in the same manner as in the various experimental examples described above, and the tensile properties were measured. In addition, since forming a mixed solution of CNF and an aqueous IPA solution is very difficult due to the handling of IPA as described above, no molded product was produced using a mixed solution of CNF and an aqueous IPA solution as a comparative example.

[0059] Sample A is the same as sample A in the reference experiment using chitin NF described above. Sample H is a sample made by simultaneously pulverizing the same PP nonwoven fabric as sample A and maleic anhydride modified polypropylene (MAHPP) to increase the compatibility of CNF and PP, then injection molding and pelletizing it, and further extrusion molding it to produce a dumbbell-shaped test piece, with the respective content ratios of PP nonwoven fabric being 95wt% and MAHPP being 5wt%. This sample H does not contain CNF.

[0060] In addition, samples I to K were prepared by immersing the same PP nonwoven fabric as sample A in a mixed solution containing an aqueous solution of CNF and surfactants (S-243 and 2303) to produce a PP nonwoven fabric with CNF attached thereto, and then pulverizing MAHPP and pelletizing them by injection molding, and further extrusion molding them to produce a dumbbell-shaped test piece. The surfactant concentrations in this mixed solution were set to 0.03 wt% for S-243 and 0.02 wt% for 2303. Sample M was prepared by using a surfactant-attached PP nonwoven fabric obtained by attaching a surfactant to a PP nonwoven fabric similar to sample A by applying the surfactant to the PP nonwoven fabric instead of immersing it in an aqueous solution of the surfactant. The compositions of samples A, H to K, and M subjected to the above-mentioned respective injection moldings are summarized in Table 5.

[0061] [Table 5]

[0062] Furthermore, the internal structures of injection-molded samples J and K were observed by electron microscope, and the results are shown in Figure 7. Figure 7(a) is an electron microscope photograph of sample J, and Figure 7(b) is an electron microscope photograph of sample K. The CNFs in sample J shown in Figure 7(a) and the CNFs in sample K shown in Figure 7(b) were both seen as flat fibrous structures dispersed throughout the cross section.

[0063] Next, a tensile test was performed using the molded test pieces A, H to K, and M. Figure 8 shows the results of the tensile test and the measurement of the tensile modulus of elasticity of the dumbbell-shaped test pieces of various samples. From the measurement results of sample A and sample H in Figure 8, there was no substantial difference in the tensile strength and tensile modulus of elasticity between sample A, which uses PP nonwoven fabric itself, and sample H, which is a PP nonwoven fabric to which MAHPP, a compatibilizer, has been added. In contrast, in samples I to M, which contain PP nonwoven fabric with CNF attached and MAHPP added, only sample I has a slightly lower tensile strength than samples A and H, but the tensile modulus is larger, and further, samples J and M have both higher tensile strength and tensile modulus than samples A and H, and the degree of increase is proportional to the amount of CNF added. In addition, sample M, which is applied rather than immersed in the mixed solution, has substantially the same tensile strength and tensile modulus of elasticity as sample K, which has approximately the same CNF concentration and MAHPP concentration.

[0064] Therefore, according to the present invention, it is possible to form a composite of natural fine materials and synthetic resins with only a small amount of surfactant, without using organic solvents such as alcohols, which are difficult to handle and require a large amount. Moreover, in the method for producing a composite of natural fine materials and synthetic resins of the present invention, a synthetic resin fiber body is impregnated or coated with a mixed solution of natural fine materials and surfactants, and then dried to form a composite fiber body with natural fine materials attached to the synthetic resin fiber body, and this composite fiber body is crushed and, if necessary, pelletized and then extruded. Therefore, there are cases where the natural fine materials are not necessarily uniformly attached to the nonwoven fabric, but the strength is almost unchanged, and even if the amount of natural fine materials added increases, the moldability is almost unchanged.

[0065] Moreover, it is possible to form a composite of naturally occurring fine materials and synthetic resins without the need for melt-kneading by twin-screw extrusion as in conventional methods, and it is also possible to easily produce a composite of naturally occurring fine materials and synthetic resins without the need for denaturing, freeze-drying, separation, chemical treatment, etc. of the naturally occurring fine materials. [Explanation of symbols]

[0066] 10...A process for preparing a mixed solution of naturally occurring fine materials and surfactants 11...Aqueous dispersion of finely divided natural materials 12...Aqueous solution of surfactant 13...Mixed solution of naturally derived fine materials and surfactants 14…Soaking process 15...Synthetic resin fiber body 16...Drying process 17...Composite fiber body 18...Crushing process 19...Synthetic resin powder with components of the mixed solution attached 20...Pelletizing process 21...Synthetic resin pellets with the components of the mixed solution attached 22...Extrusion molding process 23...Molded synthetic resin product with components of the mixed solution adhering to it

Claims

1. A method for producing a composite of a naturally occurring fine material and a synthetic resin, comprising the steps of: mixing the aqueous dispersion of the naturally occurring fine material with a surfactant to prepare a mixed solution of the naturally occurring fine material and the surfactant; impregnating or coating a synthetic resin fibrous body with a mixed solution of the naturally occurring fine material and a surfactant, and then drying the mixture to form a composite fibrous body in which the naturally occurring fine material is attached to the synthetic resin fibrous body; A step of crushing the composite fiber body and then extruding it to form a composite of a naturally occurring fine material and a synthetic resin; A method for producing a composite material of naturally occurring fine material and synthetic resin, comprising:

2. 2. The method for producing a composite of a naturally occurring fine material and a synthetic resin according to claim 1, wherein the naturally occurring fine material is chitin nanofiber, cellulose nanofiber or chitosan nanofiber.

3. 2. The method for producing a composite material of naturally occurring fine material and synthetic resin according to claim 1, wherein the surfactant is a nonionic surfactant.

4. 2. The method for producing a composite of naturally occurring fine material and synthetic resin according to claim 1, wherein the synthetic resin fibrous body is made of a thermoplastic resin.

5. A method for producing a composite of naturally occurring fine materials and synthetic resin as described in claim 1, characterized in that the process of impregnating or coating the synthetic resin fibrous body with a mixed solution of the naturally occurring fine materials and a surfactant and then drying is repeated multiple times.

6. 2. A method for producing a composite of naturally occurring fine materials and synthetic resin as described in claim 1, characterized in that it includes a step of crushing a composite fiber body having the naturally occurring fine materials attached to the synthetic resin fiber body, pelletizing the composite fiber body, and then injection molding the composite body to form a composite of the naturally occurring fine materials and synthetic resin.

7. A composite of synthetic resin and naturally occurring fine material produced by the method for producing a composite of naturally occurring fine material and synthetic resin as described in claim 6, characterized in that the naturally occurring fine material is present as a flat fibrous body.

Citation Information

Patent Citations

  • Composite particle and resin composition

    JP2021155750A

  • Bagasse fiber reinforced polypropylene resin material for injection molding, its manufacturing method and molded product

    JP4370416B1

  • Cellulose nanofiber-containing resin composition

    JP6889358B2